2016
DOI: 10.1071/fp16068
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in Fe toxicity tolerance is associated with the regulation of translocation and chelation of iron along with antioxidant defence in shoots of rice

Abstract: Excess iron (Fe) is phytotoxic and causes reduced growth and productivity in rice. In this study we elucidated the mechanisms conferring differential tolerance to Fe-toxicity in rice seedlings. Excess Fe caused retardation in roots of both Pokkali and BRRI 51, but it caused no significant changes on growth parameters, Fe accumulation and OsIRT1 expression in shoots of Pokkali only compared with control plants. These results suggest that the Pokkali genotype does have mechanisms in shoots to withstand Fe toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…GR is an important antioxidant that acts against H 2 O 2 and O 2 − [45]. Further, this enzyme is essential for GSH, an S-metabolite that protects the cell from oxidative damage [46]. This phenomenon was also consistently supported the increased GSH and cysteine accumulation in alfalfa roots, as evident by our HPLC analysis due to AMF treatment under Fe deficiency.…”
Section: Antioxidant Responses and Alleviation Of Oxidative Stress Insupporting
confidence: 79%
“…GR is an important antioxidant that acts against H 2 O 2 and O 2 − [45]. Further, this enzyme is essential for GSH, an S-metabolite that protects the cell from oxidative damage [46]. This phenomenon was also consistently supported the increased GSH and cysteine accumulation in alfalfa roots, as evident by our HPLC analysis due to AMF treatment under Fe deficiency.…”
Section: Antioxidant Responses and Alleviation Of Oxidative Stress Insupporting
confidence: 79%
“…IR64 and Inpara 5 as sensitive varieties to Fe toxicity stress, 35,36 Inpara 2 is categorized as a moderate tolerant variety to Fe toxicity stress, 36 while Pokkali is categorized as a tolerant variety. 17,[35][36][37] Fe toxicity stress disturbs metabolisms in plant, which is manifested as the formation of leaf bronzing that causes a reduction in plant growth and yield. 6,27,36,38 The bronzing symptom begins at the tips of the oldest leaves and spreads throughout the leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a five-fold increase of proline accumulation was reported in Zn-efficient RIL47 cultivar under Zn deficiency (Höller, Hajirezaei, et al 2014). Studies revealed that abiotic stress tolerance is associated with ROS scavenging via increased antioxidant defense (Alscher et al 2002;Hacisalihoglu et al 2003;Kabir et al 2016).…”
Section: Introductionmentioning
confidence: 99%